Fracture resistance of endodontically treated roots filled with resilon and guttapercha - A comparative in-vitro study - Rajesh R Shetty; Moksha Nayak; Jimmy Thomas (Wolters Kluwer Medknow Publications, 2009)
Aims and objectives: The purpose of this study was to evaluate and compare in vitro the fracture resistance of endodontically treated roots filled with Resilon and Gutta-percha. Methodology: Eighty extracted single canal teeth were selected and randomly assigned to five groups of sixteen teeth each. Teeth were sectioned using a diamond disc so as to obtain a root length of 14±1 mm. Roots were instrumented using .04 taper Profile rotary system to an apical size of 40 and obturated using .04 taper single cone (size 40) as follows: Group 1: Resilon .04 taper cone and Epiphany Self etching sealer, Group 2: .04 taper gutta-percha cone and AH Plus sealer ,Group 3: .04 taper gutta-percha cone and Roeko Seal Automix sealer, Group 4: .04 taper gutta-percha cone and Zinc oxide Eugenol sealer , Group 5: .04 taper gutta-percha cone without the use of a sealer. Following obturation, teeth were mounted in Poly Vinyl Chloride jigs using self cure acrylic resin such that 9mm of the root remained exposed. Fracture resistance testing was done using Instron testing machine using a vertical load applied perpendicular to the root surface. Statistical analysis was done using ANOVA, Tukey HSD and Student's 't' test. Results: Very highly significant difference was observed between the groups (P=.001). Resilon with Epiphany group demonstrated highest mean fracture resistance value and gutta-percha without sealer displayed the least, comparative results were highly significant. Resilon compared to gutta-percha with Roeko Seal Automix (P=.037) and Zinc Oxide Eugenolsealers (P=.029) showed statistically significant difference. AH plus group showed significantly higher value compared to gutta-percha without sealer. Conclusions: Filling the root canals with Resilon increased the in vitro fracture resistance of endodontically treated roots compared to standard gutta-percha techniques. Adhesive sealers are more beneficial in increasing the fracture resistance of endodontically treated teeth.